Improving Linkages and Referrals to the Broader Health System : For Dignified, Person-Centered Care Amidst Demographic Change - World Bank Group (World Bank, Washington, DC, 2019)
In mature health systems, specialty care systems are well developed but integration between primary care and specialty services can be poor or nonexistent, leading to missed referrals, duplication of basic diagnostics and care, long wait times, and a lack of follow-up. Forward-looking frontline services will need to develop stronger two-way linkages and referrals with specialist networks, helping ensure continuity of care from primary care to specialist appointments and hospitals, and back again to the community.